Formulation and Physical Evaluation of Kratom (Mitragyna speciosa Korth.) Leaf Extract Emulgel as Analgesic in Mice (Mus musculus) - Zulhakim, Iqmal; Kathina Deswiaqsa; Jane Arantika (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Kratom leaves contain major alkaloid compounds, particularly mitragynine and 7-hydroxymitragynine which have demonstrated anti-pain or analgesic properties. Objective: This study aims to evaluate the effectiveness of kratom leaf extract emulgel in reducing pain when applied topically in mice. Methods: This study was conducted on male mice that had been induced with acetan acid intraperitoneally. Following induction, emulgel formulations were applied topically and pain responses were recorded every five minutes over 30 minutes period. Group 1 (emulgel base without active ingredient), Group 2 (voltaren emulgel), Group 3 (emulgel with 5.6% extract concentration), Group 4 (emulgel with 11.6% extract concentration) and Group 5 (emulgel with 17.6% extract concentration).  Results: The results of physical evaluations of emulgel formulations met the applicable standards. Observations of pain responses indicated optimal analgesic effect in the emulgels containing 11.6% and 17.6% extract concentration with analgesic values of 51.52% and 63.06% respectively. An active substance is considered to have analgesic activity whent it demonstrates ≥50% effectiveness. Conclusion: This study concluded that emulgels formulated with kratom leaf extract exhibited analgesic activity as evidenced by the decreased in the writhing response of mice every five minutes.